ANALISIS SENTIMEN KOMENTAR NETIZEN TWITTER TERHADAP KESEHATAN MENTAL MASYARAKAT INDONESIA - Yan, Kenny; Arisandi, Desi; Tony, Tony (Jurnal Ilmu Komputer dan Sistem Informasi, 2022)
In today's modern era, everyone can easily exchange messages, share activities carried out in the form of images or videos using social media. Frequent use of social media can be bad for physical and mental health. Health is very important, by being healthy everyone can do activities such as studying, working, exercising, etc. Twitter as one of the social media that is widely used by the Indonesian people is used as a place to get comments that will be analyzed to find out the opinion of the Indonesian people about their mental health, this is the purpose of the analysis that has been carried out. The results obtained after analyzing the sentiments of Twitter social media users' comments on the mental health of the Indonesian people are from 2369 comment data that have been analyzed, as many as 50.8% negative, 45.1% positive and 4.1% neutral. So, it can be concluded that the sentiment analysis of social media users' comments on the mental health of Indonesian people tends to be negative. The Naïve Bayes method is used when carrying out sentiment analysis and the accuracy results are 0.7961165048543689 or rounded up to 79%.